2004
DOI: 10.1111/j.1432-1033.2004.04228.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins A‐I and A‐II are potentially important effectors of innate immunity in the teleost fish Cyprinus carpio

Abstract: We have previously shown that high density lipoprotein is the most abundant protein in the carp plasma and displays bactericidal activity in vitro. Therefore the aim of this study was to analyze the contribution of its principal apolipoproteins, apoA-I and apoA-II, in defense. Both apolipoproteins were isolated by a two step procedure involving affinity and gel filtration chromatography and were shown to display bactericidal and/or bacteriostatic activity in the micromolar range against Gram-positive and Gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 34 publications
(58 reference statements)
4
58
0
Order By: Relevance
“…Despite of primary role of APOA1 in the reverse cholesterol transport, its presence in the skin mucus and over-expression after probiotic Pdp11 administration suggest not only an extracellular role of antimicrobial activity against pathogens in gilthead seabream, as occurs in striped bass [39], but also an improving of the antimicrobial properties inferred by the Pdp11 probiotic diet. In fact, this protein has been shown to be increased in infected Atlantic salmon and Atlantic cod and showed bactericidal activity [22,34,36,40].…”
Section: Effects Of Pdp11 And/or Overcrowding Stress On Metabolism Prmentioning
confidence: 99%
“…Despite of primary role of APOA1 in the reverse cholesterol transport, its presence in the skin mucus and over-expression after probiotic Pdp11 administration suggest not only an extracellular role of antimicrobial activity against pathogens in gilthead seabream, as occurs in striped bass [39], but also an improving of the antimicrobial properties inferred by the Pdp11 probiotic diet. In fact, this protein has been shown to be increased in infected Atlantic salmon and Atlantic cod and showed bactericidal activity [22,34,36,40].…”
Section: Effects Of Pdp11 And/or Overcrowding Stress On Metabolism Prmentioning
confidence: 99%
“…In mammals, a group of nine exchangeable and soluble apolipoproteins including apoC-I, apoC-II, apoC-III, apoC-IV, apoA-I, apoA-II, apoA-IV, apoA-V, and apoE is associated with plasma lipoproteins and the structural organization of these genes is thoroughly understood [2,43,44]. Some fish apolipoproteins have been reported to have non-lipidmediated activities such as antimicrobial functions and innate immunity [11][12][13] but the structural organization of apolipoprotein genes in fish is currently limited to a very few studies [4,42]. The genetic information of fish apolipoproteins is expected to contribute not only to a better understanding of apolipoprotein evolution, but to lipid metabolism and physiology in fish lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and epidemiological studies have demonstrated an inverse correlation between the concentration of HDL-cholesterol and cardiovascular disease [7][8][9][10]. Additionally, fish apoA-I has antimicrobial and antibacterial functions [11,12], and is also an important effector of innate immunity in teleosts [13]. Therefore, the structure and functions of apoA-I gene are very important for the deeper understanding of the physiology of fish.…”
Section: Introductionmentioning
confidence: 99%
“…The 14 kDa apolipoprotein was early identified as a major component of HDL from Japanese eel (Kondo et al, 2001), and now also identified from common carp (Concha et al, 2004), pufferfish (Kondo et al, 2005), orangespotted grouper (Zhou et al, 2005), grass carp (Chang et al, 2005) and fathead minnow (Wintz et al, 2006). In common carp, the major constituents of HDL, 28 kDa ApoA-I and 13 kDa ApoA-II, were shown to display antimicrobial activity (Concha et al, 2003) and to be potentially important effectors of innate immunity (Concha et al, 2004). Kondo et al (2001) characterized three main apolipoproteins Apo-28 kDa, Apo-27 kDa and Apo-14 kDa in pufferfish, and demonstrated that Apo-28 kDa and Apo-27 kDa were homologues of mammalian ApoA-I, whereas Apo-14 was a unique apolipoprotein, and specific to fish.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that high-density lipoprotein (HDL) in teleostean fish corresponds to the most abounding plasma protein and is constituted by two major apolipoproteins which are 28 kDa apolipoprotein and 14 kDa apolipoprotein (Kondo et al, 2001;Concha et al, 2004). The 14 kDa apolipoprotein was early identified as a major component of HDL from Japanese eel (Kondo et al, 2001), and now also identified from common carp (Concha et al, 2004), pufferfish (Kondo et al, 2005), orangespotted grouper (Zhou et al, 2005), grass carp (Chang et al, 2005) and fathead minnow (Wintz et al, 2006). In common carp, the major constituents of HDL, 28 kDa ApoA-I and 13 kDa ApoA-II, were shown to display antimicrobial activity (Concha et al, 2003) and to be potentially important effectors of innate immunity (Concha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%